DIGITAL PROCESSING OF LANDSAT IMAGES TO DETECT IRONAND KAOLIN DEPOSITS IN SELECTED SITES IN THE WESTERNDESERT OF IRAQ - Abdul-Qadir, Amal; Al- Jaf, Arsalan (Iraqi Journal of Science, 2024)
The study is carried out for selected areas in the Western Desert of Iraq that arecharacterized by the occurrence of iron and kaolin mineral deposits .The study aimsto create active and suitable images to detect the mineral deposits depending on thedigital image processing for satellite images using ERDAS-9 and ARC GIS 9.1software. The study deals with ETM+ images to create image-fusion that wereprocessed to identify the spectral response of each of Iron and kaolin in the selectedareas. As well as available data of geological field survey were used to prepare the information layers associated with the attribute tables of the wells and quarries. Theresults show good agreement between remote sensing technique and the field worksurvey; a quantitative approach was established to estimate the occurrences of irondeposits in terms of spectral responses that are obtained from image processing. Irondeposits appear in yellowish green signatures on RGB (Red, Green, Blue) 4, 7, 2while Kaolin deposits appear in reddish magenta on RGB 4, 7, 5. Image fusion ofHPF (High Pass Filter) and WT (Wavelet Transform) are assigned as the mostsuitable algorithms used in the study. Image-ratio of 5/1 and 3/1 are active andsuitable to detect the light tone of iron mineral deposits, while the high spectralresponse of kaolin deposits is detected on the image of 5/7.